2006
DOI: 10.1126/science.1126675
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropenylidenes: From Interstellar Space to an Isolated Derivative in the Laboratory

Abstract: Like many of the molecular species that have been detected in the interstellar medium, the singlet carbene cyclopropenylidene (C 3 H 2 ) has been presumed to be too unstable to isolate in the laboratory. However, by appending π-electron-donating amino groups to the triangular skeleton, we prepared a cyclopropenylidene derivative that is stable at room temperature. In contrast to previously isolated carbenes, this compound does not require a heteroatom adjacent to the electron-deficient carbon to confer stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
180
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 247 publications
(200 citation statements)
references
References 30 publications
10
180
0
10
Order By: Relevance
“…After stirring for ten minutes at −78 °C, a very clean reaction occurred and crucially, a 13 C NMR signal at 167 ppm was observed. This signal is shifted to high field compared to that of the carbene carbon nucleus of the free cyclopropenylidene 4 (185 ppm), [10] exactly what is expected for a lithium complex. Indeed, it has been shown for the exceptions mentioned above, [15] that such a complexation induces an upfield shift of about 20 ppm.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…After stirring for ten minutes at −78 °C, a very clean reaction occurred and crucially, a 13 C NMR signal at 167 ppm was observed. This signal is shifted to high field compared to that of the carbene carbon nucleus of the free cyclopropenylidene 4 (185 ppm), [10] exactly what is expected for a lithium complex. Indeed, it has been shown for the exceptions mentioned above, [15] that such a complexation induces an upfield shift of about 20 ppm.…”
mentioning
confidence: 74%
“…After work up, carbene 4 was isolated in 53% yield, which compares advantageously with the 20% yield observed when the cyclopropenium salt 2, with BPh 4 as a counteranion, was used for the deprotonation reaction. [10] From these results as a whole, it appears that free cyclopropenylidene 4 cannot be generated using n-BuLi or any other lithium-containing bases. In contrast to Li + , the presence of potassium cations does not prevent the isolation of the free carbene 4.…”
mentioning
confidence: 95%
“…[3] More recently, it has been shown that bis(diisopropylamino)cyclopropenylidene (B; R = iPr) could also be isolated, [4,5] whereas B 1 , which bears very bulky aryl substituents, dimerizes to give the corresponding triafulvalene. [6] These results clearly indicate that amino groups in the b position, provided they are conjugated, can also stabilize electron-deficient centers.…”
mentioning
confidence: 99%
“…The reactivity scale of singlet carbenes encompasses exceedingly reactive molecules, such as vinylidene (H 2 C = CD), [1] as well as the well-known stable Arduengo (Wanzlick) carbenes, [2] or the recently published stable cyclopropenylidene. [3] Typical reactive singlet carbenes, such as phenoxychlorocarbene, PhOÀCÀCl, are frequently investigated workhorse molecules of physical organic chemistry [4,5] and usually have lifetimes in the microsecond range. They are generally easily prepared by thermolysis or photolysis of the corresponding diazirines (or diazo compounds).…”
mentioning
confidence: 99%